Análise comparativa de metodologias de previsão de inundação decorrente da ruptura de barragens de rejeitos: caso hipotético da Barragem Tico-Tico - Leonardo Reis de Melo (2013)
Since the publication of the Dam Safety National Policy and the regulation of its legal instruments, the risk management of Brazilian dams associated with high potential damage must make Emergency Action Plans (EAP) available. Associated with the EAPs, the hypothetical failure studies assist in the definition of mitigation actions of downstream damage. In November 2012, during the seminar "Tailings Dam Safety and Risk Management," a presentation of the Brazilian experience in studies of tailings dams failures frustrated owners of dams that have, on occasion, expressed legitimate demands for dam break studies that consider the rheological characteristics of tailings flow. In this context, the lack of criteria that delimit the dam break studies, including the tailings dams, led to the preparation of this work, which aims to compare and analyze the different methodologies of predicting impacts. Therefore, a brief review of the literature was undertaken, as well as a review of the main models that simulate tailings floods, considering their characteristics of shear strength and viscosity. Simplified models of tailings flow and force equilibrium have been applied to the case study of a hypothetical failure of the Tico-Tico dam, and compared to the hydrological and hydrodynamic models. The analysis of the results showed the difficulty of generalization of simplified models for valleys with varied geometry and steep slopes. In addition, the inconsistency of the flood parameters that resulted from these models made it impossible to delimit the flood boundaries that could assist in defining the extent of impacts. The insipience of simplified models gave the edge to the hydrodynamic models in terms of commitment to results and support for the EAP guidelines, although in some cases the flood in the valley can be overestimated.